Proceedings of the 13th International Conference on Evaluation of Novel Approaches to Software Engineering 2018
DOI: 10.5220/0006770701590168
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Influences on Requirements Engineering Process in the Context of Saudi Arabia

Abstract: Software development requires intensive communication between the requirements engineers and software stakeholders, particularly during the Requirements Engineering (RE) phase. Therefore, the individuals' culture might influence both the RE process and the result. Our aims are to investigate the extend of cultural influences on the RE process, and to analyze how the RE process can be adapted to take into account cultural aspects. The model we present is based on Hofstede's cultural theory. The model was applie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…In high PDI orientation societies the level of trust is low (Hofstede 1980;. This was also observed in the study carried out by Alsanoosy et al (2018) and Hanisch et al (2001) in Saudi Arabia (PDI=95). Trust, was however, increasingly improved when a good relationship with customers / users was established during the requirements elicitation process (Hanisch et al 2001).…”
Section: Power Distance Index (Pdi)supporting
confidence: 65%
See 2 more Smart Citations
“…In high PDI orientation societies the level of trust is low (Hofstede 1980;. This was also observed in the study carried out by Alsanoosy et al (2018) and Hanisch et al (2001) in Saudi Arabia (PDI=95). Trust, was however, increasingly improved when a good relationship with customers / users was established during the requirements elicitation process (Hanisch et al 2001).…”
Section: Power Distance Index (Pdi)supporting
confidence: 65%
“…This gap propagates the problems towards modelling/specification design and implementation of the final product, and finally may end up in the production of a system which does not meet customer needs and requirements (Damian and Zowghi 2003). Despite the importance of requirements elicitation and the problems caused by an inability to understand and meet customer/user requirements (Dijksta 1972;Alsanoosy et al 2018), insufficient attention has been paid to this area in Software Engineering (SE) research. Basic semantic differences in viewpoints may also exist when attempting to engage in meaningful dialogue between the problem owning and the problem-solving communities (Bostrum 1989).…”
Section: Related Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Culturally induced problems were the most frequent problem type reported in interviews with software professionals [14]. Cultural distance may lead to misunderstanding and misinterpretations about things that were said and done in a project, as reported by many case studies investigating Chinese professionals [15], [16], [17], [18], Irish teams outsourcing parts of their workforce to other countries [19], [20] and other teams of various culture backgrounds [21], [22]. Misunderstandings and conversational dominance of specific interlocutors due to varying levels of language proficiency can however be managed to a degree if they are recognised, e.g.…”
Section: Related Workmentioning
confidence: 99%
“…A number of studies demonstrated that the cultural diversity has to be taken into account to make the system sustainable and applicable in a global context, see [3,4,5,9,18]. In the proposed approach, we investigate how to manage the diversity of cultural and technical aspects (as well as the correlations between them).…”
Section: Introductionmentioning
confidence: 99%